38 PERIPHERAL ENDOTHELIAL FUNCTION AND CARDIOPULMONARY FUNCTION IN PATIENTS AFFECTED BY PULMONRY HYPERTENSION. (15th December 2022) - Tricarico, Lucia; Casiere, Vivian; Alfieri, Simona; Croella, Francesca; Nunno, Nicola Di; Amatruda, Marco; D´alessandro, Damiano; Granatiero, Michele; Correale, Michele; Iacoviello, Massimo; Di Biase, Matteo; Brunetti, Natale D
Abstract: Background: Pulmonary arterial hypertension (PAH) is a progressive and severe rare disease. It is a pulmonary vasculature obstructive disease that leads to right heart failure and death. Pulmonary circulation dysfunction endotelial is characterized by vasoconstriction and proliferation. Aim of study: to search possible correlations between peripheral endothelian function and cardiopulmonary function in patients with suspect PAH. Materials: Between February 2021 and May 2022, consecutive patients with suspect PAH underwent to assessment of peripheral endotelial function by FMD before of right heart catheterization and cardiopulmonary exercise testing. Results: 46 patients (22 male, 67, 9 ± 10, 4 years old) with pulmonary hypertension were enrolled in the study. The following correlations were found between stress-resting absolute difference and % difference radial diameter: ramp (r: 0, 69; p: 0, 003 and r: 0, 54; p: 0, 028, respectively), Watt_AT (r: 0, 63; p: 0, 01 and r: 0, 54; p: 0, 03, respectively) and WATT_peak (r: 0, 64, p: 0, 009). Conclusions: peripheral endothelial function may be related to funtional capacity in patients affected by pulmonary hypertension.